Origin and Affinities of the Malmberget Iron Oxide-Apatite Deposit, Northern Sweden: Insights From Magnetite Chemistry and Fe-O Isotopes - Henriksson, Jens S.; Troll, Valentin R.; Kooijman, Ellen; Bindeman, Ilya; Naeraa, Tomas; Bauer, Tobias E. (Earth Science, Systems and Society, 2024)
European iron ore production is primarily sourced from magnetite dominated iron oxide-apatite ore deposits in the northern Norrbotten ore province of northernmost Sweden. The Malmberget iron oxide-apatite deposit is at present the largest iron ore resource in Europe and is an amphibolite facies grade analogue of the world-famous Kiirunavaara iron oxide-apatite deposit. The Malmberget rock association is characterised by multiple phases of deformation, metamorphism, and alteration that resulted in a geometrically and petrologically complex deposit that is genetically ambiguous. Primary ore textures and emplacement structures of the Malmberget iron oxide-apatite deposit have largely been recrystallised during metamorphic overprinting and now comprise dominantly medium- to coarse-grained granoblastic magnetite. However, isotopic characteristics are preserved and when combined with trace element chemistry, these can be used to understand magmatic vs. hydrothermal origin of the deposit. To unravel the primary origin of the Malmberget magnetite ore, we combined magnetite trace element chemistry and Fe-O stable isotopes to investigate the massive magnetite in the Fabian-Kapten and ViRi ore bodies of the Malmberget iron oxide-apatite deposit. Trace element correlations indicate a high-temperature magmatic to a transitional high-temperature magmatic-hydrothermal origin of the Malmberget iron oxide-apatite ore deposit, with data plotting into fields of clear magmatic affinity in trace element discrimination diagrams. Fe-O data fall into established magmatic fields regardless of subsequent metamorphic modifications, underlining a dominantly (ortho-)magmatic origin of the investigated deposits. Despite an overall magmatic to magmatic-hydrothermal origin for the two ore bodies studied, Fe-O isotope equilibrium calculations of the magnetite suggest a possible temperature discrepancy between the Fabian-Kapten ore body and the ViRi ore body, the latter showing a more pronounced magmatic character. These variations in trace ...